If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(x + 2) + -43 = 1 + -29 Reorder the terms: -5(2 + x) + -43 = 1 + -29 (2 * -5 + x * -5) + -43 = 1 + -29 (-10 + -5x) + -43 = 1 + -29 Reorder the terms: -10 + -43 + -5x = 1 + -29 Combine like terms: -10 + -43 = -53 -53 + -5x = 1 + -29 Combine like terms: 1 + -29 = -28 -53 + -5x = -28 Solving -53 + -5x = -28 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '53' to each side of the equation. -53 + 53 + -5x = -28 + 53 Combine like terms: -53 + 53 = 0 0 + -5x = -28 + 53 -5x = -28 + 53 Combine like terms: -28 + 53 = 25 -5x = 25 Divide each side by '-5'. x = -5 Simplifying x = -5
| 2/7(t+2/3)=1/5(t-2/3) | | 1/2=(3-2m)/(4m-6) | | 33=y+3-0.4y | | A=a+(n-8)d | | .5(x+5)+.10*x=5.65 | | -4-3x+x^2=0 | | 3(w+8)=9w+42 | | -n=20 | | X+34=4x | | 20-2x=3.3 | | -3x+36=-9(x+2) | | X^2+2x^2=15x | | 2(x+2)=-9x+15 | | 3x=(x+64) | | 8x+16-7x=-5-13 | | 15=4.3n-2.1n+8.4 | | -2u+4=3(u-7) | | 2t^2-t+12=0 | | 8x=4(8x+12) | | 8x=(8x+12) | | 59y=29(2y+8) | | 3(y+8)+8y=35 | | 3-3=17x+12x | | 6(u-3)+4u=-38 | | 12x^2+10x+11=0 | | 29=-8w+5(w+4) | | 6(2x-1)-5x-1=14 | | 8x+1=12x | | -28=-8v+6(v-4) | | 8x+4=12x | | 3(1+4n)-2+4(3-6x)=-36 | | 1/10=4/5x+3/10 |